Development of a Wireless and Ambulatory Posture Monitoring System - Low, Eugene; Sam, Toong Hai; Tee, Kian Sek; Abdul Rahim, Ruzairi; Saim, Hashim; Wan Zakaria, Wan Nurshazwani; Mohd Khialdin, Safinaz; Isa, Hazlita; Soon, Chin Fhong (International Journal of Integrated Engineering, 2020)
The wireless and ambulatory posture monitoring system monitors the movement and posture change of the human body with respect to the g-line. It is crucial to monitor the posture health of the ophthalmologist who spends a prolonged period on the static sitting posture while operating on the slit lamp which leads to any painful experience. The motivation of the proposed system is to improve the ergonomics of the ophthalmologist on their working environment and reduce any occupational potential hazard which may prompt Work-Related Musculoskeletal Disorders (WMSDs). The proposed system also induced a wireless system by using XBee wireless units to reduce the use of the wire that may tangle on the study subject which causes any uncomfortable experience to the study subject during the human trial. Inertial Measurement Unit (IMU) sensor which consists of an Accelerometer, a Gyroscope and a Magnetometer is used to measure the angle of deviation of the body segment with respect to the g-line. The data is tabulated and presented into the graphical method to identify and extract the properties of the graph on each different static sitting posture which later are used for posture recognition.